2022
DOI: 10.1101/2022.09.28.509996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis refinement of plasma extracellular vesicle composition identifies proplatelet basic protein as a signaling messenger in type 1 diabetes

Abstract: Extracellular vesicles (EVs) play important roles in cell-to-cell communication and are potential biomarkers as they carry markers of their derived tissues and disease signatures. However, obtaining pure EV preparations from biofluids is challenging due to contaminants with similar physicochemical properties. Here, we performed a meta-analysis of plasma EV proteomics data deposited in public repositories to refine the protein composition of EVs and investigate potential roles in type 1 diabetes development. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…Our plasma sEV preparations had minute abundances of albumin (0.9941% total protein abundance) and apolipoprotein (ApoA-I, ApoA-II and ApoB100 combined, 0.0776% total protein abundance). These values are dramatically lower compared to what was reported in a recent meta-analysis investigating the protein profile of plasma EVs (note that our study used data independent acquisition (DIA) where the meta-analysis was from data acquired using data dependent acquisition MS methods) where the albumin level ranged from approximately 10-40% of the total protein abundance in the eight studies included in the meta analysis [51].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Our plasma sEV preparations had minute abundances of albumin (0.9941% total protein abundance) and apolipoprotein (ApoA-I, ApoA-II and ApoB100 combined, 0.0776% total protein abundance). These values are dramatically lower compared to what was reported in a recent meta-analysis investigating the protein profile of plasma EVs (note that our study used data independent acquisition (DIA) where the meta-analysis was from data acquired using data dependent acquisition MS methods) where the albumin level ranged from approximately 10-40% of the total protein abundance in the eight studies included in the meta analysis [51].…”
Section: Discussioncontrasting
confidence: 60%
“…Multiple studies have previously reported the proteomes [27,36,[40][41][42][43][44][45][46][47] and lipidomes of blood EV preparations [48][49][50] However, the large majority of isolation methods used in these studies would have co-isolated contaminates. It is well known that separation of abundant plasma proteins and lipoproteins from EVs is not fully achieved by common EV isolation protocols or commercial kits [51,52]. For molecular characterization therefore, albeit not suitable for use in high-throughput or clinical applications, combining DGUC with SEC is considered one of the most effective methods for obtaining highly enriched EVs [27,43,53].…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review also opens opportunities to study the functions of the biomarker candidates in T1D development and pathology. For instance, our group has found that PPBP/CXCL7 can reduce pro-inflammatory cytokine-mediated apoptosis in macrophage cell cultures while it enhances it in cultured β cells [67]. This may have a role in T1D development by potentiating macrophages and killing β cells in insulitis.…”
Section: Resultsmentioning
confidence: 99%
“…Our systematic review also opens opportunities to study the functions of the biomarker candidates in T1D development and pathology. For instance, our group has found that PPBP/CXCL7 can reduce pro-inflammatory cytokine-mediated apoptosis in macrophage cell cultures while it enhances it in cultured β cells [ 73 ]. This may have a role in T1D development by potentiating macrophages and killing β cells in insulitis.…”
Section: Discussionmentioning
confidence: 99%